PENERAPAN MODEL COURSE REVIEW HORAY DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG PECAHAN DI KELAS IV SD. - Rizki, Rahmawati Anjar (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Course Review Horay Model Using Concrete Media in Improving Mathematics Learning about Fraction for the Fourth Grade Students of SD Negeri 1 Panjer in the Academic Year of 2015/2016. The objectives of this research areto describe the steps on the application of Course Review Horay model using concrete media and to improve Mathematics learning about fraction. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Techniques of collecting data were learning outcomes observation, interview, and test. Subjects of the research were fourth grade students totaling 27 students. The conclusion of this research are: (1) the steps of the application of Course Review Horay model using concrete media, namely: delivery of competence, delivery of materials, group division, checking the answers, reading the exercise, celebration, and closing and Mathematics learning about fraction improved after the application of Course Review Horay model using concrete media.Keywords: Course Review Horay, concrete media, Mathematics Abstrak: Penerapan Model Course Review Horay dengan Media Konkret dalam Peningkatan Pembelajaran Matematika tentang Pecahan di Kelas IV SD. Tujuan penelitian ini untuk mendeskripsikan langkah penerapan model Course Review Horay dengan media konkret; dan meningkatkan pembelajaran matematika tentang pecahan. Penelitian ini merupakan PTK kolaboratif dan dilaksanakan dalam tiga siklus yang setiap siklusnya terdiri atas perencanaan, pelaksanaan, observasi, refleksi. Pengumpulan data dengan observasi, wawancara, dan tes. Subjek penelitian adalah siswa kelas IV sejumlah 27 siswa. Simpulan penelitian ini ialah: (1) langkah penerapan model Course Review Horay dengan media konkret yaitu: penyampaian kompetensi, pemberian materi, pembentukkan kelompok, pembuatan kartu, pembacaan soal, diskusi kelompok, pengecekkan jawaban, perayaan, dan penutup; dan (2) penerapan model Course Review Horay dengan media konkret dapat meningkatkan pembelajaran matematika tentang pecahan. Kata Kunci: Course Review Horay, Konkret, Matematika